1996
DOI: 10.1046/j.1365-2133.1996.d01-1004.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous manifestations of systemic lupus erythematosus

Abstract: We have assessed the cutaneous signs in 73 patients with systemic lupus erythematosus (SLE), seen during a 5-year period in an English hospital. Most previous information about the cutaneous manifestations of SLE has been obtained from studies performed in the U.S.A. We classified lesions as specific cutaneous and mucosal LE (acute, subacute and chronic) or non-specific LE-related, e.g. photosensitivity, urticaria, erythema, Raynaud's phenomenon or vasculitis. Acute cutaneous LE lesions included a butterfly ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
13

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 34 publications
6
76
0
13
Order By: Relevance
“…1), mostly appears on palms and is accompanied by local pruritus [13]. In most cases it is associated with disease activity as a single episode, although in 25% of cases it may recur.…”
Section: Palpable Purpuramentioning
confidence: 98%
“…1), mostly appears on palms and is accompanied by local pruritus [13]. In most cases it is associated with disease activity as a single episode, although in 25% of cases it may recur.…”
Section: Palpable Purpuramentioning
confidence: 98%
“…Millard and Rowell [3] described 17 cases of CHLE where 3 had concomitant SLE. Yell et al [4] reported 15 cases (20.5%) of CHLE in a large case series of SLE. Komori et al [5] described an overlap syndrome with histological features of CHLE and lichen planus in the same lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Hautveränderungen gehören zu den häufigsten initialen Symptomen des SLE [19].Charakteristisch sind hellere, meist scharf begrenzte Erytheme, die mitunter einen papulösen bzw.urtikariellen Charakter aufweisen.Typischerweise treten sie in sonnenexponierten Arealen auf, was auf die ausgesprochene Photosensitivität verweist. Zu nennen ist insbesondere das sog.…”
Section: Hautbeteiligung (70-80%)unclassified